PENGARUH KEPERCAYAAN DIRI, MINAT BELAJAR, LINGKUNGAN BELAJAR, DUKUNGAN ORANGTUA DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI - Nira Juniati; Jolianis Koto; Citra Ramayani (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Academic achievement is a key indicator of student success, but many students struggle due to low self-confidence, lack of interest in learning, unsupportive environments, inadequate parental involvement, and poor learning discipline. These challenges are evident among tenth-grade students in economics at SMAN 7 Sijunjung, where only 62% meet the minimum competency standards. This study aims to analyze the effect of self-confidence, interest in learning, learning environment, parental support, and learning discipline on students’ academic achievement. Using a quantitative approach with associative methods, data were collected from 137 students selected through proportional random sampling. Instruments used include questionnaires and documentation. The data were analyzed using multiple linear regression. The findings indicate that all five independent variables significantly influence academic achievement, both individually and collectively. However, the study is limited to a single school and subject, which may affect the generalizability of the findings. Future research is suggested to explore additional factors and broader populations.